Eucharistic Hospitality An Experiential Approach to Recent Orthodox Theology - Bordeianu, Radu (2019)
Vatican II expressed the openness of the Catholic Church to eucharistic sharing with the Orthodox Church. Orthodox observers insisted on limiting this openness but did not close the door. A survey of recent Orthodox theologians fr om the School of Paris, Zizioulas, and Staniloae shows a rift between those who are already open to eucharistic hospitality and those who precondition it on doctrinal consensus, defined variedly. An experiential approach to mixed marriages, however, shows the incongruity between uniting the spouses in Christ to form "a little church," but then requiring them to manifest ecclesial disunity in their eucharistic practices. This article proposes that Orthodox-Catholic marriages in the West become the natural place to introduce eucharistic hospitality, in the hope that this experience will have greater consequences for Church unity around the world.
Keywords: Catholic Church; Christian Union; Eucharist; Intermarriage; Orthodox Eastern Church; Orthodox Church; Theologians; Ecumenism; eucharistic ecclesiology; Hospitality; Intercommunion; Marriage